Population ageing and international development : from generalisation to evidence - Lloyd-Sherlock, P. Peter Lloyd-Sherlock (Bristol, UK ; Policy Press, 2010)
"Over the next 40 years the number of people aged 60+ in the world, many of whom live in developing regions, will grow by 10 billion. What will old age be like for them? This original book provides an analysis of links between development, population ageing and older people, challenging some widely held misconceptions. It highlights the complexity of international experiences and argues that the effects of population ageing on development are influenced by policy choices. The book will be of interest to a range of academic disciplines, including economics, gerontology, social policy and development studies as well as policy-makers and practitioners concerned with developing countries."--Publisher's description.
Includes bibliographical references and index.
Keywords: Population aging; Age distribution (Demography); Older people -- Social conditions; Older people -- Economic conditions; Economic development